متطلبات تطبيق الإدارة الالكترونية في مؤسسات القطاع العام في سوريا المصرف التجاري السوري نموذجاً - العربيد, عدنان; سلمان, حيان; خضور, أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعد تطور تكنولوجيا المعلومات (وسائل الاتصالات والأجهزة والبرمجيات) عاملا مهماً في تطور أساليب الإدارة سواء في القطاع العام أم في القطاع الخاص، وظهور مفهوم الإدارة الالكترونية، التي تقوم على سرعة تدفق المعلومات (الرقمية) واستخدام شبكة الانترنت، قد حقق تطبيقها على مؤسسات الدولة والقطاع العام قفزة نوعية في مجال العمل الحكومي وتقديم الخدمات العامة، وفي سوريا تزداد الحاجة إلى تطبيق الإدارة الالكترونية في القطاع العام بهدف تحديث وتطوير هذا القطاع الذي أصبح بحاجة إلى رفع كفاءته وتخفيض تكاليفه, والتخلص من الكثير من أمراضه وأهمها الفساد الإداري والمالي، وقد دخلت الإدارة الالكترونية إلى العديد من مؤسسات القطاع العام، وبدأت عمليات الأتمتة وإدخال قواعد البيانات في الكثير من وزارات الدولة، ومما لاشك فيه (وهذا ما سيؤكده البحث) أن الإدارة الالكترونية تلعب دورا ايجابيا بالنسبة للقطاع العام في سوريا من خلال علاقة المنظمات بعضها مع بعض من جهة، وعلاقة هذه المنظمات بالمواطنين طالبي الخدمة العامة من جهة أخرى, لذلك لابد من إلقاء الضوء على فوائد الإدارة الالكترونية ومكوناتها والعوامل المؤثرة في تطبيقها على مؤسسات القطاع العام في سوريا، وتحديد ضوابط التعاملات الحكومية الالكترونية . The development of information technology (Media, hardware and software) is an important factor in the development of methods of administration, either in the public sector or the private one. The emergence of the concept of electronic administration, represented by the speed of the (digital) information flow, the use of the Internet, and its application in the state institutions and the public sector, has made a good step in government work and the delivery of public services. In Syria, the need to implement e-governance in the public sector to update and develop it is increasing. Such implementation raises its efficiency, reduces costs, and gets rid of a number of diseases such as administrative and financial corruption. The e- administration has been used in many public sectors and institutions. Automation operations and database design in many ministries have been done. There is no doubt that the electronic administration plays a positive role in the public sector in Syria by carrying out transactions among organizations on one hand, and by organizing the relations of these organizations with the citizens who need these services on the other hand. So it is important to highlight the benefits of electronic administration and its components, to determine factors influencing its application in the public sector institutions in Syria, and to identify controls over electronic governance transactions